2019
DOI: 10.2147/ccid.s217956
|View full text |Cite
|
Sign up to set email alerts
|

<p>Identification Of Three Key Factors Contributing To The Aetiology Of Dark Circles By Clinical And Instrumental Assessments Of The Infraorbital Region</p>

Abstract: Background: The aetiology of infraorbital dark circles is complex and multi-factorial. The aim of this research was to measure and characterize dark circles and to determine the physiological changes associated with the occurrence of this aesthetically unpleasing issue. Materials and methods: Clinical, photographic and instrumental assessments were performed on Caucasian skin to determine the most appropriate methodologies to measure dark circles, comparing different zones of the infraorbital region in subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 19 publications
1
14
0
1
Order By: Relevance
“…Although there was also a slight change in grade in the untreated eyes at 8 weeks, the net difference between treated and untreated was 0.59, and crucially, there was a continuous decrease in the grade over the treatment period. A slight change is the untreated eye is not entirely unexpected, as we have previously observed temporal fluctuations in the appearance of dark circles [3]. Our data have shown that changes in grade of greater than 0.5 correspond to ΔE values of between 1 and 2, which is within the range perceivable to the human eye and therefore the mean treatment change observed in the clinical trial is consumer relevant.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Although there was also a slight change in grade in the untreated eyes at 8 weeks, the net difference between treated and untreated was 0.59, and crucially, there was a continuous decrease in the grade over the treatment period. A slight change is the untreated eye is not entirely unexpected, as we have previously observed temporal fluctuations in the appearance of dark circles [3]. Our data have shown that changes in grade of greater than 0.5 correspond to ΔE values of between 1 and 2, which is within the range perceivable to the human eye and therefore the mean treatment change observed in the clinical trial is consumer relevant.…”
Section: Discussionsupporting
confidence: 78%
“…The aetiology of infraorbital dark circles is complex; causal factors include excessive pigmentation because of melanin deposition, vasodilation and venous stasis, thinner skin of the eyelids and structural features of the orbital area [3–5]. This can be compounded by the ageing process, which results in skin sagging and altered subcutaneous fat distribution [1–7]. In addition, numerous intrinsic and extrinsic factors have been associated with their occurrence [8, 9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of them are distributed symmetrically in all age groups. At present, most of the drugs for the treatment of dark circles are expensive and ineffective [3][4][5][6][7] . Yurong powder comes from Qianjin Yaofang, which can remove blackness and brighten skin color.…”
Section: Introductionmentioning
confidence: 99%